2013
DOI: 10.1007/s10654-013-9832-9
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and premature all-cause mortality

Abstract: Events causing stress responses during sensitive periods of rapid neurological development in childhood may be early determinants of all-cause premature mortality. Using a British birth cohort study of individuals born in 1958, the relationship between adverse childhood experiences (ACE) and mortality ≤50 year was examined for men (n = 7,816) and women (n = 7,405) separately. ACE were measured using prospectively collected reports from parents and the school: no adversities (70 %); one adversity (22 %), two or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
201
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(226 citation statements)
references
References 35 publications
(40 reference statements)
6
201
0
4
Order By: Relevance
“…In this context, the study of the relationship between ACE and AL can contribute to a better understanding of early origins of disease and social gradient in health. Recently, Kelly-Irving et al (28,29) showed an association between ACE and self-reported cancer as well as mortality, after adjusting for behavioral and socioeconomic factors suggesting …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the study of the relationship between ACE and AL can contribute to a better understanding of early origins of disease and social gradient in health. Recently, Kelly-Irving et al (28,29) showed an association between ACE and self-reported cancer as well as mortality, after adjusting for behavioral and socioeconomic factors suggesting …”
Section: Discussionmentioning
confidence: 99%
“…Lately, epidemiological studies have shown that ACEs were associated with mortality and health even after adjusting for socioeconomic and behavioral factors, suggesting that a direct biological effect occurring from early life is plausible (28,29). It has been suggested that psychosocial factors could protect and buffer early adverse circumstances, such as parental warmth and psychological resources, reducing physiological responses and mitigating disease processes (30,31).…”
Section: Significancementioning
confidence: 99%
“…No increased mortality between age 27 and 69 y was found in the 1,726 members of the Helsinki Birth Cohort (born 1934-1944 and followed from 1971-2003) who were separated as children from their parents during the Second World War (32). In the 1958 British birth cohort, increased all-cause mortality before age 50 y was found for the 4,543 individuals who experienced events such as parental divorce or bereavement in early life (33).…”
mentioning
confidence: 92%
“…For instance, males born at the height of the Finnish famine lost ∼1 y of life expectancy at age 40 y (29). To our knowledge, only two studies have related early psychological stress and adult mortality (32,33). No increased mortality between age 27 and 69 y was found in the 1,726 members of the Helsinki Birth Cohort (born 1934-1944 and followed from 1971-2003) who were separated as children from their parents during the Second World War (32).…”
mentioning
confidence: 96%
“…Faire la part des différentes expositions englobées dans ce terme de niveau socioéconomique précoce reste un enjeu important. Des travaux ont récemment mis en évidence le lien entre l'adversité durant l'enfance, incluant les abus (physiques, sexuels, émotionnels), les négligences (physiques, émotionnelles) ou des dysfonctionnements familiaux, et le risque de mortalité prématurée [9] ou de cancer [10] à l'âge adulte. Ce lien était certes atténué après prise en compte des facteurs de confusion -tels que l'environnement pré-et périnatal -, et de médiation à l'âge adulte -tels que les comportements à risque, la santé mentale ou le niveau socioéconomique -, mais il persistait, rendant plausible un effet biologique précoce de l'adversité qui reste à expliciter.…”
Section: Les Enjeux Liés Aux Modifications Du Statut Nutritionnel Matunclassified